Inverse and Square Root of Positive Definite Matrices
📂Matrix Algebra Inverse and Square Root of Positive Definite Matrices Let’s say the eigenpairs { ( λ k , e k ) } k = 1 n \left\{ \left( \lambda_{k} , e_{k} \right) \right\}_{k=1}^{n} { ( λ k , e k ) } k = 1 n of a positive definite matrix A A A are arranged in order λ 1 > ⋯ > λ n > 0 \lambda_{1} > \cdots > \lambda_{n} > 0 λ 1 > ⋯ > λ n > 0 . Regarding the orthogonal matrix P = [ e 1 ⋯ e n ] ∈ R n × n P = \begin{bmatrix} e_{1} & \cdots & e_{n} \end{bmatrix} \in \mathbb{R}^{n \times n} P = [ e 1 ⋯ e n ] ∈ R n × n and the diagonal matrix Λ = diag ( λ 1 , ⋯ , λ n ) \Lambda = \diag \left( \lambda_{1} , \cdots , \lambda_{n} \right) Λ = diag ( λ 1 , ⋯ , λ n ) , the inverse matrix A − 1 A^{-1} A − 1 and the square root matrix A \sqrt{A} A of A A A are as follows:
A − 1 = P Λ − 1 P T = ∑ k = 1 n 1 λ k e k e k T A = P Λ P T = ∑ k = 1 n λ k e k e k T
\begin{align*}
A^{-1} =& P \Lambda^{-1} P^{T} = \sum_{k=1}^{n} {{ 1 } \over { \lambda_{k} }} e_{k} e_{k}^{T}
\\ \sqrt{A} =& P \sqrt{\Lambda} P^{T} = \sum_{k=1}^{n} \sqrt{\lambda_{k}} e_{k} e_{k}^{T}
\end{align*}
A − 1 = A = P Λ − 1 P T = k = 1 ∑ n λ k 1 e k e k T P Λ P T = k = 1 ∑ n λ k e k e k T
Derivation Spectral Decomposition :
Spectral Theory : It is equivalent that A A A is a Hermitian matrix and can be unitarily diagonalized :
A = A ∗ ⟺ A = Q Λ Q ∗
A = A^{\ast} \iff A = Q \Lambda Q^{\ast}
A = A ∗ ⟺ A = Q Λ Q ∗
In particular, in statistics , covariance matrices are often positive definite matrices and positive definite matrices are Hermitian matrices . Not just covariance matrices but also with respect to a design matrix X X X , X T X X^{T} X X T X is a symmetric matrix , especially if X ∈ R m × n X \in \mathbb{R}^{m \times n} X ∈ R m × n , it becomes a Hermitian matrix again. Under these conditions, according to spectral theory, A A A can obtain Q Q Q , which consists of orthonormal eigenvectors e 1 , ⋯ , e n e_{1} , \cdots , e_{n} e 1 , ⋯ , e n , restated as follows:
A = Q Λ Q ∗ = Q [ λ 1 0 ⋯ 0 0 λ 2 ⋯ 0 ⋮ ⋮ ⋱ ⋮ 0 0 ⋯ λ n ] [ e 1 ∗ e 2 ∗ ⋮ e n ∗ ] = [ e 1 e 2 ⋯ e n ] [ λ 1 e 1 ∗ λ 2 e 2 ∗ ⋮ λ n e n ∗ ] = λ 1 e 1 e 1 ∗ + λ 2 e 2 e 2 ∗ + ⋯ + λ n e n e n ∗ = ∑ k = 1 n λ k e k e k ∗
\begin{align*}
& A
\\ = & Q \Lambda Q^{\ast}
\\ = & Q \begin{bmatrix}
\lambda_{1} & 0 & \cdots & 0
\\ 0 & \lambda_{2} & \cdots & 0
\\ \vdots & \vdots & \ddots & \vdots
\\ 0 & 0 & \cdots & \lambda_{n}
\end{bmatrix} \begin{bmatrix} e_{1}^{\ast} \\ e_{2}^{\ast} \\ \vdots \\ e_{n}^{\ast} \end{bmatrix}
\\ = & \begin{bmatrix} e_{1} & e_{2} & \cdots & e_{n} \end{bmatrix} \begin{bmatrix} \lambda_{1} e_{1}^{\ast} \\ \lambda_{2} e_{2}^{\ast} \\ \vdots \\ \lambda_{n} e_{n}^{\ast} \end{bmatrix}
\\ = & \lambda_{1} e_{1} e_{1}^{\ast} + \lambda_{2} e_{2} e_{2}^{\ast} + \cdots + \lambda_{n} e_{n} e_{n}^{\ast}
\\ = & \sum_{k=1}^{n} \lambda_{k} e_{k} e_{k}^{\ast}
\end{align*}
= = = = = A Q Λ Q ∗ Q λ 1 0 ⋮ 0 0 λ 2 ⋮ 0 ⋯ ⋯ ⋱ ⋯ 0 0 ⋮ λ n e 1 ∗ e 2 ∗ ⋮ e n ∗ [ e 1 e 2 ⋯ e n ] λ 1 e 1 ∗ λ 2 e 2 ∗ ⋮ λ n e n ∗ λ 1 e 1 e 1 ∗ + λ 2 e 2 e 2 ∗ + ⋯ + λ n e n e n ∗ k = 1 ∑ n λ k e k e k ∗
Since Λ \Lambda Λ is a diagonal matrix, there’s nothing special to derive. Since P P P is an orthogonal matrix,
A − 1 = ( P Λ P T ) − 1 = P − T Λ − 1 P − 1 = P Λ − 1 P T
\begin{align*}
A^{-1} =& \left( P \Lambda P^{T} \right)^{-1}
\\ =& P^{-T} \Lambda^{-1} P^{-1}
\\ =& P \Lambda^{-1} P^{T}
\end{align*}
A − 1 = = = ( P Λ P T ) − 1 P − T Λ − 1 P − 1 P Λ − 1 P T
and the following verification yields A \sqrt{A} A with respect to the identity matrix I I I :
( P Λ P T ) ( P Λ P T ) = P Λ P T P Λ P T = P Λ I Λ P T = P Λ Λ P T = P Λ P T = A
\begin{align*}
& \left( P \sqrt{\Lambda} P^{T} \right) \left( P \sqrt{\Lambda} P^{T} \right)
\\ =& P \sqrt{\Lambda} P^{T} P \sqrt{\Lambda} P^{T}
\\ =& P \sqrt{\Lambda} I \sqrt{\Lambda} P^{T}
\\ =& P \sqrt{\Lambda} \sqrt{\Lambda} P^{T}
\\ =& P \Lambda P^{T}
\\ =& A
\end{align*}
= = = = = ( P Λ P T ) ( P Λ P T ) P Λ P T P Λ P T P Λ I Λ P T P Λ Λ P T P Λ P T A
■